Tuberculosis spondylitis in patients on hemodialysis: Clinical features, risk factors, and outcomes in 12 patients. Issue 1 (4th May 2020) - Zhang, Jianna; Zhang, Ji; Sun, Mei; Zhou, Qiongxiu; Liu, Yi; Chen, Chaosheng; You, Xiaohan
Abstract: The aim of this study was to investigate the clinical features, risk factors and outcomes of tuberculosis spondylitis (TBS) in patients on hemodialysis (HD). We systematically reviewed medical records from 12 HD patients with TBS admitted to our hospital from April 2008 to April 2018. A total of 120 age‐ and sex‐matched HD patients without infections were randomly selected as controls. The incidence of TBS in our patient group was 1.5/1000 per year. The average duration from initial symptoms to diagnosis was 45.4 days (range, 11‐180 days). Neurosurgery was performed in 4 (33.3%) patients. TBS was cured or improved in 11 (91.7%) patients. HD patients with TBS had significantly lower albumin and Hb levels than controls ( P = .03 and P = .01). These findings indicated that lower albumin and Hb levels were possible risk factors for TBS in patients on HD, most HD patients with TBS had a good outcome after anti‐TB therapy with or without surgery.